Carbon dioxide (CO2 ) emissions and mitigation efforts based on Bogor City's green open space - Wardhani, Annisa Choerinita Kusuma; Retnowati, Rita; Istiadi, Yossa (Universitas Pakuan, 2024)
One of the risks associated with climate change is carbon dioxide (CO2) emission, which can negatively affect human health and the ecosystem. The CO2 emission can lead to a decline in urban area quality that surpasses the environment's carrying capacity. This research aimed to investigate the relationship between CO2 Emissions from Transportation (X1), Household (X2), and Business Sector (X3) with the CO2 reduction of green open space (Y). The hypothesis is that there is a negative correlation between CO2 emissions from transportation, households, and businesses and CO2 reduction from green open spaces. A quantitative research design was adopted using the Slovin formula and cluster random sampling. The Normality and Homogeneity Tests are used to analyze research data. The study yielded the following results: first, the coefficient of determination (r2) = 0.003 indicates a relationship between CO2 emissions from transportation with CO2 reduction from green open space, with a 0.3% contribution. The second finding is that there is a 0.1% contribution from CO2 reduction from green open space to the CO2 emissions of households, as indicated by the coefficient of determination (r2) = 0.001. Third, a correlation of 0.1% between CO2 reduction from green open space and CO2 emissions from the Business Sector is indicated by the coefficient of determination (r2) = 0.001. Thus, using the regression equation Y = 2320.432 – 0.16X1 – 0,25 X2 – 0,007 X3, there is an overall significant relationship between CO2 emissions from transportation, CO2 emissions from households, and CO2 emissions from the business sector with the reduction of CO2 from green open space. Salah satu risiko yang terkait dengan perubahan iklim adalah emisi karbon dioksida (CO2), yang dapat berdampak negatif terhadap kesehatan manusia dan ekosistem. Hal ini dapat mengakibatkan penurunan kualitas kawasan perkotaan hingga melampaui daya dukung lingkungan. Penelitian ini bertujuan untuk mengetahui hubungan Emisi CO2 dari Transportasi (X1), Rumah Tangga (X2), dan Dunia Usaha (X3) dengan penurunan CO2 pada Ruang Terbuka Hijau (Y). Hipotesisnya adalah terdapat korelasi negatif antara emisi CO2 dari transportasi, rumah tangga, dan dunia usaha dengan penurunan CO2 dari ruang terbuka hijau. Dengan menggunakan rumus Slovin dan cluster random sampling, desain penelitian yang digunakan adalah kuantitatif. Uji Normalitas dan Homogenitas digunakan untuk menganalisis data penelitian. Penelitian ini menghasilkan hasil sebagai berikut: pertama, koefisien determinasi (r2) = 0,003 menunjukkan adanya hubungan antara emisi CO2 dari transportasi dengan penurunan CO2 dari ruang terbuka hijau, dengan kontribusi sebesar 0,3%. Temuan kedua, terdapat kontribusi penurunan CO2 dari ruang terbuka hijau terhadap emisi CO2 rumah tangga sebesar 0,1% yang ditunjukkan dengan koefisien determinasi (r2) = 0,001. Ketiga, korelasi sebesar 0,1% antara penurunan CO2 dari RTH dengan emisi CO2 dari Dunia Usaha ditunjukkan dengan koefisien determinasi (r2) = 0,001. Dengan demikian, dengan menggunakan persamaan regresi Y = 2320.432 – 0.16X1 – 0,25 X2 – 0,007 X3, secara keseluruhan terdapat hubungan yang signifikan antara emisi CO2 dari transportasi, emisi CO2 dari rumah tangga, dan emisi CO2 dari dunia usaha dengan penurunan emisi CO2 dari ruang terbuka hijau.